Group theoretical methods and applications to molecules and crystals - Kim, Shoon Kyung, 1920- (Cambridge University Press, 1999)
"This book explains the basic aspects of symmetry groups as applied to problems in physics and chemistry using an approach pioneered and developed by the author. The symmetry groups and their representations are worked out explicitly, eliminating the unduly abstract nature of group theoretical methods."--BOOK JACKET. "This work will be a of great interest to graduate students and professionals in solid state physics, chemistry mathematics and geology and to those who are interested in magnetic crystal structures."--Jacket